(NmIKROSTROENIE MERZLYH POROD (B/s - (NeR[OW(B, (N|DUARD dMITRIEWI^s; (NlEBEDENKO(B, (N`(B.(Np(B.s; (N~UWILIN(B, (Ne(B.(Nm(B.s; (NqZYNIN(B, (No(B.(Nm(B.s; (NeR[OW(B, (N|DUARD dMITRIEWI^s ((NmOSKWA (B:s (Nmgu(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 179-181s
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (NgORNYE PORODY MERZLYEs; (NmIKROSTRUKTURAs